Female genital mutilation of minors in Italy: is a harmless and symbolic alternative justified? (Italian Journal of Public Health, 2012)
In 2004, Omar Abdulcadir - a gynecologist of the Centre for the prevention and therapy of female genital mutilation (FMG) at the Careggi Hospital (Florence) - proposed a “harmless and symbolic” alternative to FMG, which consists in the puncture of the clitoris under local anesthesia, in order to allow the outflow of some drops of blood (1).The intention behind the symbolic alternative is to avoid more severe forms of FGM while respecting cultural heritage. The proposal of this alternative procedure, which was sustained by the leaders of 10 local African immigrant communities, has encountered ample criticism (1).However, the question is: is the puncture of the clitoris prohibited by the Italian Law n. 7/2006? If it is not, could it be considered a method of reducing health risks caused by the more invasive forms of FGM (2)? Or could it culturally legitimize FGM, causing a greater difficulty in the attempts to prevent and eradicate FGM in Italy?
Keywords: Female genital mutilation; Minors; Symbolic alternative; Italian law